Investigation of the antifungal activity of some non-antifungal drugs in clinical isolates of otomycosis: In vitro study - Muhsin, Rana; Muhsin, Rana (University of Thi-Qar Journal of Science, 2012)
Otomycosis is one of the commonly encountered problems in otolaryngology practice. Treatment of otomycosis is challenging, and requires a close follow-up; in addition treatment with classical topical orsystemic antifungal drugs might be associated with problems of resistance, mucosal irritation, and systemic toxicities, such problems necessitate finding new approaches and cellular targets that can beattacked by new drugs. Proton pump, calcium channels and mitotic spindle are potential targets. Aim of this study is to investigate the antifungal activity of some non-antifungal drugs, namely lansoprazple (proton pump inhibitor), verapamil (calcium channel blocker), albendazole and mebendazole(antihelminthic drugs) against clinical isolates of otomycosis.Ear swaps were collected from 18 patientswith otomycosis attending otolaryngology outpatient clinic-Al-Habboobi Hospital. Fungal identification was done depending on microscopical and colonial morphology. Antifungal effect of the tested drugs was assessed by agar well-diffusion assay. Eighteen samples were examined, 13 (72%) of them were positive for fungal growth, 6 were Aspergillus niger , 1 was Aspergillus flavus, 2 were Candida albicans,and the other 4 were Non- albicans Candida.lansoprazole, verapamil, albendazole and mebendazoleshowed significant antifungal activity at the tested concentrations against Aspergillus niger, Aspergillusflavus, and fluconazole resistant Candida albicans and Non- albicans Candida.